Analisis Tingkat Kepatuhan Wajib Pajak Orang Pribadi Serta Kontribusinya pada Penerimaan Pajak Studi Kasus KPP Pratama Jakarta Pancoran Tahun 2018-2020 - Ratih Juwita (STIE Jambatan Bulan, 2022)
ABSTRAK The purpose of this study is to determine the level of compliance of individual taxpayers (WP OP) and to find out how big their contribution is to the tax revenue of the KPP Pratama Jakarta Pancoran case study in 2018-2020. This research uses descriptive quantitative and qualitative descriptive analysis methods. The results of this study indicate that the level of compliance of Individual Taxpayers (WP OP) Employees and Non-Employees at KPP Pratama Jakarta Pancoran is still relatively low. This condition is supported by the fluctuating ratio of individual taxpayers' annual tax returns (WP OP) for employees and non-employees due to the fact that there are still many taxpayers who do not understand the procedures for filling and calculating the annual tax return. In addition, the level of compliance of Individual Taxpayers (WP OP) Employees and Non-employees has a positive contribution to tax revenue at KPP Pratama Jakarta Pancoran. This shows that the more compliant Individual Taxpayers (WP OP) Employees and Non-Employees in the KPP Pratama Jakarta Pancoran in reporting the Annual SPT have a big impact on tax revenues for the local KPP